Implementasi Algoritma Hybrid dan Metode Least Significant Bit Untuk Keamanan Data - Ibnu Sulistyo; Eko Aribowo (Jurnal Informatika: Jurnal Pengembangan IT, 2020)
Computer networks can improve the quality of communication; however, it also allows accessing data illegally. Unauthorized access to people’s data can cause harm. In order for the data to remain safe, the cryptographic algorithm encryption process is needed. Nevertheless, there is also a disadvantage of encryption which can lead to suspicions. To get rid of unnecessary suspicion, there is a need for steganography algorithms, and one way of making sure that it is hidden is by using the least significant bit method. This research uses a hybrid algorithm and the least significant bit technique. Hybrid algorithm models are used for better security before being concealed under the image, and the only way of doing that is by using least significant bit method. The types of image files used are PNG and JPG or JPEG. The success rate of this experiment is 100%, with eight tests that have been done with a maximum insertion of 5000 characters.